A cardiac manifestation in patients with COVID-19: a case series - Ravindranath, Archita; Ramaiah, Madhumati; Kadloor, Parvaiz (International Journal of Advances in Medicine, 2020)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus or the coronavirus 2019 (COVID-19) infection is a novel viral infection causing the 2020 pandemic affecting primarily the respiratory system in the form of influenza like illness, severe acute respiratory illness or asymptomatic respiratory illness and other systems. The cardiovascular system may also be affected, with or without a prior history of cardiovascular diseases. Myocardial injury is common among patients hospitalized with COVID-19 due to stress cardiomyopathy, hypoxic injury, ischemic injury due to cardiac microvascular damage or epicardial coronary artery disease and cytokine storm, however rhythm abnormalities is affected rarely in a transient or severe manner causing rhythm disturbances. The concerns about COVID‐19 may result in a delay in proper approach and prompt management in many emergent medical conditions, such as cardiovascular problems. Here, we describe our experience with 4 COVID-19 patients with varied cardiac manifestations presenting to our hospital during the months of September- October 2020.